METODE INTERPRETASI ZOOSEMIOTIKA SASTRA AL-QUR’AN DAN APLIKASINYA DALAM SURAT AL-MUDDAṠṠIR AYAT KE 50-51 - Mushodiq, Muhamad Agus (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
Discrimination and ill-treatment of animals are still ongoing today. In the Islamic world, this is allegedly the result of a non-holistic interpretation of religious texts. This paper aims to formulate a literature zoosemiotic interpretation method of the Qur'an and apply it to Surah al-Muddaṡṡir verses 50-51. The method is formulated to explore the meaning of animal verses in the Qur'an holistically and proportionally. There are two results of the research in this article. First, the steps of the literary zoosemiotics interpretation method refer to (1) determining the typology of animals in the Qur'an based on literary zoological themes, (2) outlining asbāb al-nuzūl micro-macro and makiyyah-madaniyyah letters. (3) conducting a study of munāsabah al-āyāt, intratextual, and intertextuality, (4) reviewing the results of previous mufasir interpretations, (5) describing the meaning of the word verse with semiotics and balāgah, and (6) efforts find zoosembiology (reciprocity) between the Qur'anic literature and zoology and conclude the relevance between animal literature and human life. Second, based on the new myth, the ḥumur ‘donkeys’ in Surah al-Muddaṡṡir verses 50-51 describes the fanaticism of the tribes and the degree of opposition of the Quraysh to the da'wah of the Prophet Muhammad, not the symbol of ignorance that exists in the old myth.